Capital market indicators and their impact on banking sector performance in Nigeria - Godswill Osuma; Abieyuwa Ohonba (Cogent Business & Management)
This study investigates the impact of capital market indicators on the performance of Deposit Money Banks in Nigeria from 1993 to 2023. Key capital market variables examined include stock market size (market capitalisation), stock price movements (All-Share Index), stock market liquidity (value of shares traded relative to GDP), and treasury bill rates. The study adopts the Autoregressive Distributed Lag (ARDL) model to assess short- and long-run relationships. Findings reveal a significant long-run cointegration between capital market development and banking sector performance. Stock market size positively and significantly influences bank growth, indicating that deeper capital markets enhance banking intermediation. However, in the short run, fluctuations in stock prices and market liquidity negatively impact bank growth, suggesting that capital market volatility may pose risks to banking operations. The Error Correction Model confirms a moderate speed of adjustment toward equilibrium, reinforcing the long-term relationship. The study highlights the complementary role of capital markets and banks in Nigeria’s financial system. It recommends strengthening regulatory frameworks, improving market transparency, and fostering investor confidence to enhance capital market development and ensure sustained growth in the banking sector. This research contributes to literature by offering sector-specific insights into the capital market–banking performance nexus in emerging economies.